OBJEKTIFITAS DAN RASIONALITAS PENAFSIRAN AL-QUR’AN: PERSPEKTIF AL-JĀBIRĪ - Abdullah Affandi (IAIN Kediri, 2015)
Qurâ€™anic Studies had been developed according to the changing times. Scholars have offered many differentÂ methods to reveal Godâ€™s messages in the Qurâ€™an. Different methods and approaches were used by a number ofleading scholars. â€˜Ä€bid al-JÄbirÄ« is among those leading scholars who focus on this study. In his works of MadkhalÂ ilÄ al-Qurâ€™Än and Fahm al-Qurâ€™Än, al-JÄbirÄ« cultivates historically the Qurâ€™anic discourse and interpretationÂ and suggests a new method of understanding the Qurâ€™an. Using a philosophical-historical approach, this paperÂ examines the fundamental ideas of al-JÄbirÄ« in the Qurâ€™anic discourse and in interpretation methodology.Keywords: Objektifikasi, Rasionalisasi, Tafsir al-Qurâ€™an